Electronic Behavior of GaN Nanowire Photocathode Surface Coated with n‐Type GaN Capping Layer via First Principles. Issue 12 (6th October 2022) - Lu, Feifei; Liu, Lei; Tian, Jian; Zhangyang, Xingyue; Cheng, Hongchang; Guo, Xin
Abstract : Conventional negative electron affinity photocathodes require alternate activation of Cs/O, and the instability of Cs makes the cathode surface easily inactive. A Cs‐free GaN photocathode structure is reported, in which band engineering of the photocathode surface induced by Si doping eliminates the need to use Cs for photocathode activation. This heterojunction structure can obtain a low‐barrier surface without activation. GaN nanowires with n‐type capping layers are established using first principles, and their stability, work function, and optoelectronic structures are analyzed. Si atoms replace Ga atoms more easily, thereby forming an n‐type capping layer. The formation energy of the n‐type capping layer of the nanowires surface is lower than that of the surface capping layer of the thin film. The addition of the n‐type capping layer reduces the work function of the GaN surface, which will help to enhance photoemission capability. The results clearly illustrate the positive effect of the n‐type capping layer on the electronic properties of the device, so this Cs‐free activation structure can be further considered. Abstract : GaN nanowires with n‐type capping layers are investigated. Si atoms are more likely to substitute Ga atoms to form an n‐type capping layer. n‐Type capping layer reduces the work function of the GaN material. The addition of Si atoms increases the possibility of charge transfer. Si atoms provide shallow donor energy level in the n‐type GaN capping layer.